Food safety risk assessment in beef in Arusha municipality, Tanzania - Mahundi, E.; Kurwijila, Lusato R.; Karimuribo, E.D.; Makita, K.; Ngowi, H.E.; Grace, Delia (Tanzania Food and Drugs Authority, 2011)
BACKGROUND: Thermophilic Campylobacter is one of the most important pathogen causing food borne illness in the world. In Tanzania, the risks of campylobacteriosis had not been studied yet and the risks especially from informally marketed foods are in a great need for assessment. A study on risk assessment for Thermophilic Campylobacter infection through consumption of ready to eat beef in Arusha was therefore carried out from January to March 2010. METHODS: A total of 160 samples were collected from beef carcasses (swabs) in butcher (n=73) and roast beef (nyama choma in Swahili language) (n=45; one gram pieces) and skewer beef (mishikaki) (n=42, one gram pieces) sold in beer bars. All the samples were served for isolation of thermophilic Campylobacter spp. The number of customers per hour was recorded in nine nyama choma and nine mishikaki centres for seven consecutive days. A risk model for assessing risk of campylobacteriosis due to the consumption of ready-to-eat beef was developed in @Risk (Palisade) and these data were fed into it. Dose-Response relationship was modeled using reported variables in literatures. Immunity against thermophilic Campylobacter for adults was modeled using the diarrhoeal data in a hospital reported in a separate study. Monte Carlo simulation was run for 10,000 iterations and sensitivity analysis was run for 63 simulations in 1000 iterations. RESULTS: The overall contamination rate of ready-to-eat beef with thermophilic Campylobacter was 24%. The probability of consuming contaminated meat with thermophilic Campylobacter at nyama choma pubs was 15.5% and at mishikaki shops was 34.7%. The total amount of beef sold at nyama choma pubs in Arusha municipality per day was 3,595 kg (90% CI: 1,745-6,173) and that sold as mishikaki per day was 165 kg (90% CI: 57-328). The probability that a naturally immunized person develops illness when he/she ingests enough dose of thermophilic Campylobacter causing illness to a susceptible person was 13.1% by point estimate. Risk characterization showed that the incidence rate of campylobacteriosis in Arusha per day was estimated as 6.43 people (90%CI:3.4-10.4) per 1000 people. Sensitivity analysis found that the most sensitive risk input was initial population of Campylobacter in ready-to-eat beef which we did not study in the present study. SUMMARY: Contamination of carcasses with Campylobacter spp has indicated the need of applying good hygienic standards at all levels from farm to table in order to ensure food wholesomeness and safety in beef. Public education programmes, consumer awareness and training of food handlers on general food hygiene are recommended to reduce potential health risks to the public. Additional studies on the concentration of Campylobacter in different stages of value chain especially on the surfaces of ready-to-eat beef is required to update the present study for the more reliable risk characterization.